Analisis Perbandingan Kinerja Keuangan Perbankan Sebelum Dan Saat Pandemi Covid-19 Menggunakan Analisis RGEC Pada Bank BUMN (Bank Umum Persero) Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2020 - Fatimah, Siti; Yacobus, Aryono; Nurohim, Hasa (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research was motivated by the Covid-19 virus which spread to Indonesia and caused a pandemic outbreak. The impact of the Covid-19 pandemic on the banking sector is related to the level of financial health of banks in Indonesia. This study aims to determine the level of financial health of banks, especially BUMN Banks (Persero Banks) before the Covid-19 pandemic and during the Covid-19 pandemic in 2020 using RGEC analysis (Risk Profile, Good Corporate Governance, Earning and Capital).The data analysis tool method used is SPSS (Statistical Package for Social Sciences).The results of this study prove that there is no significant difference in banking financial performance between before and during the 2020 Covid-19 Pandemic at BUMN Banks (Persero) as measured by the ratio Risk Profile. There is no significant difference in the financial performance of banks between before and during the 2020 Covid-19 Pandemic in BUMN Banks (Persero) as measured by the ratio Good Corporate Governance. There is a difference in the financial performance of banks between before and during the 2020 Covid-19 Pandemic in BUMN Banks (Persero) as measured by the ratio Earnings. There is no difference in banking financial performance between before and during the 2020 Covid-19 Pandemic at State-Owned Banks (Persero) as measured by the ratio Capital.